The influence of venous tumor thrombus combined with bland thrombus on the surgical treatment and prognosis of renal cell carcinoma patients - Zhuo Liu; Li Zhang; Peng Hong; Liwei Li; Shiying Tang; Xun Zhao; Qiming Zhang; Guodong Zhu; Ran Peng; Binshuai Wang; Zhigang Chen; Zhenghui Sun; et al. (Cancer Medicine, 2020)
Abstract Objective To describe the clinical characteristics of renal cell carcinoma (RCC) with venous tumor thrombus (VTT) and bland thrombus (BT), and to evaluate the influence of BT on surgical treatment and cancer‐specific survival (CSS) of RCC with VTT. Methods We retrospectively reviewed clinical data of 123 patients with RCC and VTT, who underwent surgical treatment in our center between February 2015 and May 2018. Patients were divided into the BT group (21 patients) and non‐BT group (102 patients). Chi‐square and Mann‐Whitney U test were used for categorical and continuous variables respectively. Univariable log‐rank tests and multivariable Cox regressions were conducted to evaluate the prognostic significance of each variable. Kaplan‐Meier plots were performed to evaluate the influence of BT. Results In the delayed phase of enhanced magnetic resonance imaging (MRI), BT and VTT had difference. Patients were divided according to the relative position of BT: proximal end BT (one patients), contralateral renal vein BT (two patients), distal end BT (12 patients), and multiple BT (six patients). The average length of BT was 8.4 ± 5.8 cm (range: 0.6‐20.0 cm). Patients with BT had longer operative time (P = .001), more surgical blood loss (P = .004), higher proportion of open surgery (P = .006), more postoperative complications (P = .011). BT (hazard ratio [HR] = 3.323, P = .007) were independent risk factors for poor prognosis. Conclusions In the delayed phase of enhanced MRI, BT showed no obvious enhancement, while VTT usually showed enhancement. This was an important basis for preoperative imaging diagnosis of BT. The presence of BT increases the difficulty of surgery, and is correlated with adverse survival outcomes in patients with RCC and VTT.